2020
DOI: 10.1002/cctc.202000471
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Substrate Binding Residues on the Substrate Scope and Regioselectivity of a Plant O‐Methyltransferase against Flavonoids

Abstract: Methylation of free hydroxyl groups is an important modification for flavonoids. It not only greatly increases absorption and oral bioavailability of flavonoids, but also brings new biological activities. Flavonoid methylation is usually achieved by a specific group of plant O‐methyltransferases (OMTs) which typically exhibit high substrate specificity. Here we investigated the effect of several residues in the binding pocket of the Clarkia breweri isoeugenol OMT on the substrate scope and regioselectivity aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 21 publications
0
13
0
2
Order By: Relevance
“…The T133M-Y326L variant of isoeugenol O-MT (IeOMT) and the V140T AtHMT catalyzed regioselective mono-ethylation of luteolin to 3'-O-ethylluteolin (6) with 41 % conversion. [15] Similarly, human catechol O-MT (COMT) in cascade with V140T AtHMT catalyzed regioselective mono-allylation of 3,4dihydroxybenzaldehyde to produce 4-allyloxy-3hydroxybenzaldehyde (8) with 48 % conversion (Table S5). [16] The identities of the products were confirmed by 1 H and 13 C NMR spectroscopy (Figures S12-S17).…”
Section: Kinetic Analysis (Figuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The T133M-Y326L variant of isoeugenol O-MT (IeOMT) and the V140T AtHMT catalyzed regioselective mono-ethylation of luteolin to 3'-O-ethylluteolin (6) with 41 % conversion. [15] Similarly, human catechol O-MT (COMT) in cascade with V140T AtHMT catalyzed regioselective mono-allylation of 3,4dihydroxybenzaldehyde to produce 4-allyloxy-3hydroxybenzaldehyde (8) with 48 % conversion (Table S5). [16] The identities of the products were confirmed by 1 H and 13 C NMR spectroscopy (Figures S12-S17).…”
Section: Kinetic Analysis (Figuresmentioning
confidence: 99%
“…Therefore, we used the V140T At HMT for in vitro regeneration of SAE, SAP, and SAA, from catalytic amounts of SAH, in one‐pot biocatalytic alkylation cascades (Figure 3 b). The T133M–Y326L variant of isoeugenol O ‐MT (IeOMT) and the V140T At HMT catalyzed regioselective mono‐ethylation of luteolin to 3′‐ O ‐ethylluteolin ( 6 ) with 41 % conversion [15] . Similarly, human catechol O ‐MT (COMT) in cascade with V140T At HMT catalyzed regioselective mono‐allylation of 3,4‐dihydroxybenzaldehyde to produce 4‐allyloxy‐3‐hydroxybenzaldehyde ( 8 ) with 48 % conversion (Table S5) [16] .…”
Section: Figurementioning
confidence: 99%
“…This indicates a similar orientation and binding mode for DIMBOA-Glc and flavonoid substrates in the active sites of these enzymes. Previous publications showed that the substrate preference, regiospecificity, and overall activity of FOMTs can be altered by a few amino acid mutations in the substrate binding pocket [ 16 , 43 , 44 ]. Using homology modeling and amino acid sequence comparisons, we identified nine putative active site residues that differ between flavonoid 5- and DIMBOA-Glc 4-OMTs ( Figure 3 , Figures S4 and S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Methyltransferase 6) mit 41 % Umsatz. [15] Ebenso katalysierte die humane Catechol-O-MT (COMT) in einer Kaskade mit V140T-AtHMT die regioselektive Monoallylierung von 3,4-Dihydroxybenzaldehyd, um 4-Allyloxy-3-hydroxybenzaldehyd (8) bei 48 % Umsatz zu bilden (Tabelle S5). [16] Die Identität der Produkte wurde über 1 H-und 13 Wir haben gezeigt, dass das Spektrum biokatalytischer Alkylierungen rasch durch Ausnutzung der Promiskuität einer optimierten Halogenid-Methyltransferase erweitert werden kann.…”
Section: Varianteunclassified
“…Daher verwendeten wir die V140T‐ At HMT für die In‐vitro‐Regenerierung von SAE, SAP und SAA mit katalytischen Mengen von SAH in Eintopf‐biokatalytischen Alkylierungskaskaden (Abbildung 3 b). Die T133M‐Y326L‐Variante der Isoeugenol O ‐MT (IeOMT) und die V140T‐ At HMT katalysierten die regioselektive Monoethylierung von Luteolin zu 3′‐ O ‐Ethylluteolin ( 6 ) mit 41 % Umsatz [15] . Ebenso katalysierte die humane Catechol‐ O ‐MT (COMT) in einer Kaskade mit V140T‐ At HMT die regioselektive Monoallylierung von 3,4‐Dihydroxybenzaldehyd, um 4‐Allyloxy‐3‐hydroxybenzaldehyd ( 8 ) bei 48 % Umsatz zu bilden (Tabelle S5) [16] .…”
Section: Figureunclassified